Impact of Role Conflict and Role Ambiguity on Emotional Exhaustion among Non-Managerial Employees in Boutique Hotels in Nepal - Ojha , Gaurav (Journal of Innovation in Academia, 2025)
This study investigates the impact of role conflict and role ambiguity on emotional exhaustion experienced by employees working at a non-managerial level in different boutique hotels operating inside the Kathmandu Valley. Non-managerial employees are an essential part of the boutique hotel segment and its overall functioning, efficiency, and effectiveness. This study applies a cross-sectional survey design along with descriptive and multiple-regression analysis. According to data analysis, role conflict among non-managerial employees in boutique hotels is positively and significantly related to emotional exhaustion, while the link between role ambiguity and emotional exhaustion is positive but not statistically significant. Importantly, to reduce the stressful experiences germinating from role conflict and role ambiguity, which contribute to the prevalence of emotional exhaustion, this study implies that boutique hotels need to implement efficient HRM policies and practices that provide job descriptions, areas of specialization, job specifications, and performance agreements to their non-managerial employees.